Factors associated with high turnover of Jordanian physicians in rural areas: a sequential exploratory mixed method study - Khatatbeh, Moawiah (Curtin University, 2013)
Background: The high turnover of physicians in rural areas of Jordan, a low-middle income country in the Middle East, has adversely affected the provision of primary health care. This study was undertaken in an effort to understand the reasons for this high turnover and to inform health policy makers to formulate more effective strategies to counter this problem which also affects many developing and developed countries around the world. Methods: A sequential exploratory mixed method design was chosen for the study with the data collection in two phases. In the first phase, qualitative data was gathered using focus group interviews. Four focus groups were considered and each group consisted of five participants. Participants in the focus groups were purposefully sampled and represented currently posted rural physicians, previously posted rural physicians, health directors, and consumers of health services from the general rural community. In the second quantitative phase, a cross-section of currently posted Jordanian rural physicians was surveyed using a 98-item questionnaire whose design was informed by findings from the first qualitative phase. A total of 307 completed questionnaires were elicited in this survey. Qualitative data were analysed with the help of the QSR-NVivo 8 software using thematic analysis, while quantitative data were analysed with SPSS version 19, using both descriptive and analytical statistical procedures including frequency distributions, Chi-Square Tests and logistic regression. Results: Due to the cross-sectional observational nature of the study design, it was not possible to prospectively measure turnover rate among currently working physicians, rather intention-to-leave was used as an indicator of turnover. By this measure, the overall intention to leave rural practice among the currently employed rural physicians in Jordan was 29.3%. A large number of personal, organizational, work related and socio-cultural factors were identified and found to be associated with turnover of rural physicians. Some of these factors V have been reported in the previous literature; however, others were specific to the Jordanian context. Factors revealed during focus group discussions included - financial incentives, professional development, workload issues, rural background of medical practitioners and rural exposure during training, transportation issues, demographic characteristics of participants, management related factors, social isolation of rural physicians, lack of treatment facilities, poor general services, lack of resources, lack of opportunities for spouses’ career development and socio-cultural characteristics of the Jordanian community. A framework of the association between the various factors associated with turnover of rural physicians was established from the qualitative phase. Findings from the quantitative phase complemented the factors documented in the qualitative phase, and in addition identified physician’s age, method of appointment to work sites, daily travelling time, workload, satisfaction about referral policy, and social isolation as significant factors affecting turnover. Conclusion: Physicians in rural Jordan are dissatisfied with a large range of organizational, social and personal factors. These factors could lead to a high rate of physicians’ turnover and therefore impede the quality of health services offered to rural communities. A number of recommendations were formulated to inform decision makers and health policy planners to address the issue of high physician turnover in rural Jordan. In addition, the study generated directions for future research, especially through cohort or prospective studies, to track progress in the area and to evaluate the impact of both organizational and personal factors on physician turnover.